TANGGUNG JAWAB PENGANGKUT TERHADAP KESELAMATAN DAN KEAMANAN BARANG DALAM KAPAL - Dekie GG Kasenda (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Transportation is a very important field of activity in public life Indonesia. he importance of transport for the people of Indonesia are caused by several factors, among others, the geographical situation of Indonesia which consists of thousands of small and large, the waters that comprise the bulk of the sea, rivers and lakes that allows transport is made by land, water and air to reach all areas of Indonesia. he responsibility of the carrier to the safety and security of goods in the ship, has been strictly regulated in Article 40 and Article 41 of Law No. 17 Year 2008 on the voyage. The responsibility of the carrier may be incurred as a result of the operation of the ship, destroyed, lost or damaged goods or delays in transportation of passengers and / or freight. If the transport company that can prove that the loss was not caused by his fault, transport companies may be exempted from some or all of its responsibilities.